Implementation of Counseling and Education on the Success of Exclusive Breastfeeding of Mother Who Breastfeed a Baby with a History of LBW in Yogyakarta - Ria Febrina (Universitas Batanghari Jambi, 2019)
In the Special Region of Yogyakarta (DIY), the Infant Mortality Rate (IMR) is 25 per 1000 live births, the most common causes of infant mortality in DIY are low birth weight (LBW) and sepsis. LBW is most commonly found in Sleman Regency as many as 823 babies. One of the management of LBW babies is exclusive breastfeeding. Exclusive breastfeeding coverage in Yogyakarta City in 2015 was 71.62%. The purpose of this study is to obtain information on the differences in the success of exclusive breastfeeding between counseling and education. In addition, it is to understand the relationship of extraneous variables (age, education, occupation, parity) with the success of exclusive breastfeeding in mothers who breastfeed a baby with a history of LBW.The type of this research was Quasi-Experimental, Posttest Only Control Design, using breastfeeding mother respondent who had a 4-months-old baby with a history of LBW as much as 51 people, sample as much as 30 people based on minimum sample size for the experiment. The location of the research was in 14 working area of community health center in Sleman Regency. The determination of the samples in each location was determined based on Proportional Random Sampling. The instrument used in determining the success of exclusive breastfeeding was a questionnaire. The data obtained were analyzed using Wilcoxon Sign Rank Test and Chi-square test with a significance level of 0.05.The results showed no significant difference in the success of exclusive breastfeeding between the groups of counseling and education (p-value 0.414). Education and parity had a significant relationship to the success of exclusive breastfeeding (p-value 0.003 and p-value 0-016).